RELASI PATRONASE DALAM PERKEBUNAN KARET RAKYAT - Pahrudin Pahrudin (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
A social relation in the form of patronclient has been living for a long time in A social relation in the form of patronclient has been living for a long time in human live. No wonder if there is almost no sector or aspect of human live in the earth which is untouched by this relational pattern. For instance; agricultural, holticultural or fihing sectors are also inflenced by this patronage relation. Many experts defie that the relational pattern of patronclient as the integrated relation between individual each other or groups and individuals or other groups in which one party’s position is as a patron or a boss while the other party’s position is as a client or a staff. This relational pattern has been done by many people those who involved in it through goods or services exchanging. A patron usually has resources which are badly needed by their clients. Soon after that they exchange one another with the other goods or services they have, for instance. This relational pattern has been living though the benefi obtained is not the same. Even it tends to make a party’s position as a patron that gets benefi more than it’s client. This writing discusses about the pattern and the form of patronclient relation in managing rubber holticultural in Rantau Limau Manis Village, Jambi. Also discusses the determining factors of the continuing patronclient relation in managing rubber agricultural in this village. From this discussion the writer gets the fact that a patron client relation in managing the rubber agricultural in this village is performed by exchanging resources from the owner of the garden of rubber holticultural with the rubber wiretapping services from the rubber wiretapper. This relational pattern has been living until they get the benefi respectively, both material and nonmaterial. Though from the outside perspective, this is unbalance, but people those who involved expecially the clients, in this business are not aware. Even they get more benefi from this. However, the writer fids the fact that there are four factors become the determiner of the continuing of this relational pattern; the limiting of alternative jobs, the expensive of rubber price, the applying of paternalistic feudal system in the society and the mastering of rubber holticultural from certain people. These four determining factors are related each other so that the relational pattern of patronage have been still standing and developing in the society until now.